PERANCANGAN SISTEM MONITORING DAN CONTROLLING SMART HOME BERBASIS INTERNET OF THINGS - Abdul Hakim Prima Yuniarto; Yuni Lestiyanti; Aflah Nurcholis; Feriawan Feriawan; Recha Nofillah (Universitas Riau, 2022)
The design of the Internet of Things-based Smart Home monitoring and control system has been successfully carried out. This design aims to control and monitor electronic equipment in the classrooms of the ITS NU Pekalongan lecture building. The design begins with designing a microcontroller consisting of NodeMCU ESP8266 and relays that are connected to electronic equipment. Monitoring and controlling is done through the telegram bot on the telegram messenger application. The system is connected via the internet network, so it can be accessed anywhere and anytime. System testing is done by testing the functions of all the buttons on the telegram bot interface and calculating the response time to determine the delay of the system. Based on the test results, all buttons on the Smart Home system function and run properly without any errors or errors that occur. In measuring response time, the Smart Home system runs smoothly with relatively sort delay times.